Religious tolerance in South East Asean countries: issues and prospects - Wahyono, Zubaidi; Gamon, Alizaman Dumangcag; Tagoranao, Mariam Saidano (2020)
In today’s world, religious tolerance has been a crucial issue be it in the Muslim majority countries or non-Muslim countries. The current debate on the issues of the freedom of religion, conversion, freedom of worship and propagation, and violence are mainly triggered by religious misunderstandings such as extremism and terrorism. The objective of the study is to understand how the national policies of Malaysia, Indonesia, and the Philippines had been formed to give a public space for religious tolerance which opens the door for the protection of freedom of religion and other religious issues that are currently taking place in the region. Besides, the study seeks to investigate the root causes of extremism, terrorism, and religious conflict. Aware of the breadth and width of the study, the different perspectives on the dimensions of religious tolerance and the various strategies in maintaining multiculturalism will be examined with the aid of the current researches on the issues as well as observations. Apart from that, field research and interviews will be conducted to reconfirm the veracity of the information received from various sources. It is the highlight of the study to understand religious tolerance as reflected in the constitution, national laws or policies of the said countries as well as their implementation at the social level. Suggestions on how to improve the practices of religious tolerance and ways to maintain a meaningful co-existence in this age of cultural and religious pluralism will be crafted within the paradigm of securing a lasting peace. Initially, the study discovered that intolerance, extremism, conflicts, and violence that have taken place at various degrees in the region are more often than not driven by economic, social, and political factors rather than the religious one. Therefore, the study opines the view that it is an erroneous belief to attribute problematic issues such as conflict, violence, and extremism with the teachings of a particular religion and Islam especially that uphold the message of ‘rahmatan lil ‘alamin, a mercy for the entire humanity.